1990
DOI: 10.1056/nejm199009133231104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age at the Start of Iron Chelation Therapy on Gonadal Function in β-Thalassemia Major

Abstract: Beginning chelation treatment with deferoxamine before the age of puberty can help children with transfusion-dependent thalassemia major to attain normal sexual maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
2
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(72 citation statements)
references
References 31 publications
3
61
2
6
Order By: Relevance
“…13 In the present study, there was no overt hypothyroidism in our patients with BTM, the result which agreed with that of Bronspiegel-Weintrobe et al 1990, 14 but the study of Aydinok et al 2002 11 declared that 17-18% of their patients with betathalassemia have hypothyroidism. IGF1 was statistically significantly lower in our children patients with BTM than the control group p<0.03, the result which agreed with that of DeLuca et al 1995, 15 who attributed this low level to disturbed liver function secondary to iron overload and malnutrition.…”
Section: Discussionsupporting
confidence: 82%
“…13 In the present study, there was no overt hypothyroidism in our patients with BTM, the result which agreed with that of Bronspiegel-Weintrobe et al 1990, 14 but the study of Aydinok et al 2002 11 declared that 17-18% of their patients with betathalassemia have hypothyroidism. IGF1 was statistically significantly lower in our children patients with BTM than the control group p<0.03, the result which agreed with that of DeLuca et al 1995, 15 who attributed this low level to disturbed liver function secondary to iron overload and malnutrition.…”
Section: Discussionsupporting
confidence: 82%
“…The prevalence of hypogonadism and/or delayed puberty was reported at 40%-80% [3,4] by previous studies. This prevalence depended on serum ferritin levels, type of thalassemia, the onset of blood transfusion and chelating therapy [4,7,13,14]. We had no patients with abnormal testicular function or delayed puberty in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to adequate treatment with blood transfusion at an appropriate time (3.8 ± 2.3 years old) and effective iron chelation shown by a mean serum ferritin level during the past year of 1,575 ± 642 ng/mL. Bronspiegel-Weintrob et al [13] reported that patients with abnormal puberty had higher serum ferritin levels before chelation and had received suboptimal chelation therapy (serum ferritin levels 4,734 ± 3,081 and 3,572 ± 1,870 ng/mL, respectively). Important factors for developing hypogonadism and/ or delayed puberty are a high serum ferritin level [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common complication of iron loading in thalassemia, hypogonadism, is also prevented by effective use of deferoxamine (Bronspiegel-Weintrob et al 1990), although secondary amenorrhea in women, and secondary hypogonadism in men, may develop after age 21, even in those who have attained normal puberty (Gamberini et al 2008). …”
Section: Clinical Benefitsmentioning
confidence: 99%